2021
DOI: 10.1038/s41598-020-80596-4
|View full text |Cite
|
Sign up to set email alerts
|

The amphibian peptide Yodha is virucidal for Zika and dengue viruses

Abstract: Zika virus (ZIKV) has emerged as a serious health threat in the Americas and the Caribbean. ZIKV is transmitted by the bite of an infected mosquito, sexual contact, and blood transfusion. ZIKV can also be transmitted to the developing fetus in utero, in some cases resulting in spontaneous abortion, fetal brain abnormalities, and microcephaly. In adults, ZIKV infection has been correlated with Guillain–Barre syndrome. Despite the public health threat posed by ZIKV, neither a vaccine nor antiviral drugs for use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 38 publications
0
24
0
1
Order By: Relevance
“…The Structure and NA Activity of the Influenza Virus Are Unaffected by OSCN − . Physical damage to the viral envelope has been described as part of the mechanism of antimicrobial peptides (33). We therefore asked whether OSCN − leads to similar, physical changes in influenza viruses.…”
Section: Duox1-derived H 2 O 2 Promotes Influenza Virus Inactivation In Normalmentioning
confidence: 99%
“…The Structure and NA Activity of the Influenza Virus Are Unaffected by OSCN − . Physical damage to the viral envelope has been described as part of the mechanism of antimicrobial peptides (33). We therefore asked whether OSCN − leads to similar, physical changes in influenza viruses.…”
Section: Duox1-derived H 2 O 2 Promotes Influenza Virus Inactivation In Normalmentioning
confidence: 99%
“…However, it is necessary to investigate which domain of the ZIKV envelope is targeted by BR2GK. This domain is speculated to have some conserved motifs and can be recognized by BR2GK, and it contributes to understanding why amphibians, rich in AMPs, have not been reported to be infected by ZIKV [17]. Molecular docking showed that BR2GK can bind to the E stem domain of the ZIKV envelope protein, which may indicate a direction for further research.…”
Section: Discussionmentioning
confidence: 93%
“…Antimicrobial peptides (AMP) from amphibians are an important source of antiviral peptide drugs [12][13][14][15][16], of which brevinins are a family with significant pharmacological activity. In addition to significant antibacterial activity, brevinins have also been reported to have antiviral activity against HSV, HIV, and ZIKV [17][18][19]. In order to further expand the medicinal values of brevinins, we screened some brevinins for their antiviral activity.…”
Section: Introductionmentioning
confidence: 99%
“…The antiviral action of Brevinins was described recently. The peptide called Yodha, belonging to the Brevinin family, contains 23 amino acids (SMLLLFFLGTISLSLCQDDQERC) and has antiviral action against Dengue virus and Zika virus ( Lee et al, 2021 ). This peptide, which was isolated from Indosylvirana aurantiaca skin, has its amino acids with hydrophobic side chains dominating almost half of the N-terminal region, and the C-terminus contains three negatively charged amino acids ( Lee et al, 2021 ).…”
Section: Anurans Peptides Against Human Virusesmentioning
confidence: 99%
“…Some recent studies have been projected bioinformatics interactions between anuran skin peptides sequences against SARS-CoV-2 searching for possible antiviral action against this new coronavirus ( Fakih, 2020 ; Fakih et al, 2020 ; Liscano et al, 2020 ). The use of computational tools have been essential to better understand the viral infection, the immune response, and to development new treatments and vaccines candidates efficiently against SARS-CoV-2 ( Lee et al, 2021 ; Sharma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%